PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER UNTUK MENCEGAH MATHOPHOBIA SISWA DI KECAMATAN PASIR SAKTI - Bambang Ariyanto; Sasmito Adi; Mar’atus Sholehah (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2016)
Feelings of fear of mathematics often come to students from elementary to tertiary level, so this problem is often considered very crucial compared to other fields of study. This is supported by the fact that shows that not a few students who consider mathematics is a subject that makes stress, makes the mind confused, time-consuming and tend to only fiddle with formulas that are not useful in life. As a result, mathematics is seen as a science that does not need to be learned and can be ignored. Supported by a learning process that is oriented to the course of practice questions. The process of learning mathematics is often not directly related to real life. In response to this, one thing that is immediately done is how to make students happy to learn mathematics. Feelings of fear of mathematics lessons experienced by students at this school in this study are called mathopobia. The research method used is quasi experiment. The population used is elementary school students in the Pasir Sakti District with samples of Islamic elementary school Al Firdaus, SDN 1 Semarang Baru, SDN2 Semarang Baru and SD Baitul Ibad Pulo Sari. Data obtained through a questionnaire and then analyzed using SPSS 20. 1. Based on the output spss shows that the value of t0 with t t (t table) obtained numbers: 2.09 for significance of 5% and 2.86 for significance of 1%. With t0 -2.708 means greater than 2.09, but smaller than -2.6. (2.09 <2.708 <2.86). So the hypothesis is rejected at the 5% level and accepted at the 1% level. In conclusion, students' mathematics learning skills only affect the significance level of 5% and not at the level of 1%. 2. Based on the output spss shows that t0 with t t (t table) with df = 19 obtained numbers: 2.09 for significance of 5% and 2.86 for significance of 1%. With t0 - 1,978 means it is smaller than 2.09 and from -2.86. (2.09> -1.978 <2.86). So the null hypothesis is accepted at the 5% level and accepted at the 1% level. In conclusion, the students' attitude to learning mathematics has no effect on the significance level of 5% or at the level of 1%. 3. Based on the output spss shows that t0 with tt (t table) with df = 19 obtained numbers: 2.09 for significance of 5% and 2.86 for significance of 1%. With t0 -2,021 means greater than 2.09, but smaller than -2.6. (2.09 <-2,021 <2.86). So the hypothesis is rejected at the 5% level and accepted at the 1% level. In conclusion the application of learning together learning models of mathematics only affects the significance level of 5% and not at the level of 1%.